Further Evidence That People Rely on Egocentric Information to Guide a Cursor to a Visible Target. (October 2021) - Crowe, Emily M.; Bossard, Martin; Karimpur, Harun; Rushton, Simon K.; Fiehler, Katja; Brenner, Eli
Everyday movements are guided by objects' positions relative to other items in the scene (allocentric information) as well as by objects' positions relative to oneself (egocentric information). Allocentric information can guide movements to the remembered positions of hidden objects, but is it also used when the object remains visible? To stimulate the use of allocentric information, the position of the participant's finger controlled the velocity of a cursor that they used to intercept moving targets, so there was no one-to-one mapping between egocentric positions of the hand and cursor. We evaluated whether participants relied on allocentric information by shifting all task-relevant items simultaneously leaving their allocentric relationships unchanged. If participants rely on allocentric information they should not respond to this perturbation. However, they did. They responded in accordance with their responses to each item shifting independently, supporting the idea that fast guidance of ongoing movements primarily relies on egocentric information.